β-Human Chorionic Gonadotropin Dynamics in Early Gestational Events: A Practical and Updated Reappraisal - Demetrio Larraín; Javier Caradeux (Hindawi Limited, 2024)
In the last decade, the widespread use of transvaginal ultrasound and the availability of highly specific serum assays of human chorionic gonadotropin (hCG) have become mainstays in the evaluation of early pregnancy. These tests have revolutionized the management of pregnancies of unknown location and markedly reduced the morbidity and mortality associated with the misdiagnosis of ectopic pregnancy. However, despite several advances, their misuse and misinterpretations are still common, leading to an increased use of healthcare resources, patient misinformation, and anxiety. This narrative review aims to succinctly summarize the β-hCG dynamics in early gestation and provide general gynecologists a practical approach to patients with first-trimester symptomatic pregnancy.